(untitled) (Journal of the College of Basic Education, 2022)
The study included 24 patients compared to 16 healthy controls. The results showed a significant increase in the concentration of tumor necrosis factor-alpha TNF-α in infected children (101.71 ± 3.91 pg / ml) compared to healthy children (83.94 ± 1.60 pg / ml), while a non-significant increase appeared in the level of IL-17 in infected children (164.06 ± 5.56 pg / ml) compared to healthy subjects (161.79 ± 4.42 pg / ml). Also, there was a non-significant correlation between TNF-alpha and leukemia 17. From this we conclude that TNF-alpha has a major role in defending the body against amoeba infection. The condition of the tissue and there is no significant correlation between the studied cellular kinetics